2022
DOI: 10.3390/v14092061
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Binding Domain (RBD) Antibodies Contribute More to SARS-CoV-2 Neutralization When Target Cells Express High Levels of ACE2

Abstract: Neutralization assays are experimental surrogates for the effectiveness of infection- or vaccine-elicited polyclonal antibodies and therapeutic monoclonal antibodies targeting SARS-CoV-2. However, the measured neutralization can depend on the details of the experimental assay. Here, we systematically assess how ACE2 expression in target cells affects neutralization by antibodies to different spike epitopes in lentivirus pseudovirus neutralization assays. For high ACE2-expressing target cells, receptor-binding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The target cell line for different antibodies is determined by whether an antibody is able to neutralize pseudovirus on that cell line. We have previously described this phenomena in (Farrell et al, 2022) where we show that non-ACE2 competing antibodies do not fully neutralize pseudovirus on ACE2 overexpressing cells. While testing antibodies for the current study we also noticed that some S2-targeting antibodies are also not affected by ACE2 overexpression.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The target cell line for different antibodies is determined by whether an antibody is able to neutralize pseudovirus on that cell line. We have previously described this phenomena in (Farrell et al, 2022) where we show that non-ACE2 competing antibodies do not fully neutralize pseudovirus on ACE2 overexpressing cells. While testing antibodies for the current study we also noticed that some S2-targeting antibodies are also not affected by ACE2 overexpression.…”
Section: Methodsmentioning
confidence: 79%
“…HEK-293T were acquired from ATCC (CRL3216), HEK-293T-ACE2 cells are described in (Crawford et al, 2020), generation and characterization of HEK-293T-ACE2-medium cells is described in (Farrell et al, 2022) (referred to ‘medium’ cells in the reference), generation of HEK-293T-rtTA cells is described below. All cells were grown in D10 media (Dulbecco’s Modified Eagle Medium with 10% heat-inactivated fetal bovine serum, 2 mM l-glutamine, 100 U/mL penicillin, and 100 μg/mL streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“… 26 Preclinical findings also observed that two doses of mRNA-1283 administered at lower dose levels than mRNA-1273 elicited higher nAb titers and bAb responses in mice, which may be due to greater antigen expression with mRNA-1283 at lower dose levels. 18 In addition, antibodies to the RBD and NTD regions are the primary contributors to the neutralization response observed in pseudovirus assays, 27 , 28 and the design of mRNA-1283 to focus the immune response to these 2 regions may shift the dose-dependent response of the vaccine to dose levels lower than 10 µg. Whether these findings extend to T-cell responses in humans is currently being assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The viral titer was determined by infecting HEK293T-ACE2 cells and measuring relative luciferase units (RLUs). The HEK293T-ACE2 cells used express high levels of ACE2 as described previously (55, 99).…”
Section: Methodsmentioning
confidence: 99%